A study Concerning Islamic Law Courts, Conditions and the Development of Implemented Laws in Palestine - Abdel-Karim Jaber Ali Toafshh (My University, 2014)
This study dealt with the reality of religious courts and the development of the enforced laws in Palestine, as a result, this study was divided into three chapters. To begin with, the first chapter talked about the history of the religious courts in Palestine in terms of their initiation and division from the other courts. Then, it talked about the concept of religious courts linguistically that it explored the development of religious courts in the shadow of the Ottoman state, the Israeli occupation, the British mandate and the Palestinian Authority (PA). After that, it talked about the spectrum of religious courts, namely: trial courts, appellate courts, Supreme religious court. It also talked about Supreme Court (hereinafter referred to as SC) of the religious law, the personal status persecution and the religious courts in 1948 Palestine. In addition, it explored the jurisdiction of those courts and the kind of cases it dealt with. This study started with defining the word “law” linguistically focusing on the legality of law in Quran and Sunnah. Then, it clarified the religious point of view of enforcing laws and the reasons behind doing so highlighting the responsibilities of the judges. This chapter was concluded with the difficulties that face working in the religious courts. The second chapter talked about the personal status laws which were enforced in the religious courts in Palestine. It started with talking about the enforced laws in the West Bank especially the personal status law number 61, which was issued in 1976. Then, the laws, which were enforced in Gaza, were explored especially the law of family rights number 303 which was issued in 1954. This chapter was concluded by talking about the enforced laws in the religious courts in 1948 Palestine especially what is related to the family’s right and the book of the religious and personal status laws of Qadri Basha. The third chapter talked about the personal status modifications in the religious courts in Palestine that this study explored the modified and added provisions in the West Bank, Gaza and 1948 Palestine. Finally, this study tackled the suggested provisions in the Palestinian personal status law project. The reasons behind that were clarified along with the positive and procedural laws which the project treats. Then, the researcher concluded this study with the results and conclusions. On the one hand, there are two main conclusions, namely: 1. The jurisprudence of law is the one which was enforced in the Palestinian religious courts in the Ottoman period. 2. The other courts left cases such as marriage and divorce to the religious court. Concerning the issues of homicide, they are dealt with the civil court. On the other hand, there are three main recommendations, namely: 1. It is necessary to implement the laws of the Islamic law on every aspect of Muslims’ daily life. 2. It is necessary to unify law in Palestine that it should be religious in order to solve all the disagreements 3. It is necessary to unify the laws, which are enforced in the religious courts in the West Bank and Gaza, based on the Islamic creed. Finally, the researcher added the list of the references and table of content of the study.

لقد تناولت في رسالتي هذه واقع المحاكم الشرعية وتطور القوانين المعمول بها في فلسطين فجعلت رسالتي من ثلاثة فصول، فتكلمت في الفصل الأول عن تاريخ المحاكم الشرعية في فلسطين منذ نشأتها وانفصالها عن باقي المحاكم، فتطرقت إلى مفهوم المحاكم من الناحية اللغوية والناحية الاصطلاحية، ثم استعرضت المحاكم في الدولة العثمانية، والمحاكم الشرعية أثناء الانتداب البريطاني، والمحاكم الشرعية زمن الاحتلال الإسرائيلي، والمحاكم الشرعية في عهد السلطة الوطنية الفلسطينية، وكذلك تكلمت عن درجات المحاكم الشرعية التي تتكون من محاكم ابتدائية، ومحاكم استئنافية، والمحكمة العليا الشرعية، وكذلك تكلمت عن المجلس الأعلى للقضاء الشرعي، وعن نيابة الأحوال الشخصية، ومن ثم عن المحاكم الشرعية في فلسطين المحتلة عام 1948م، وكذلك استعرضت صلاحيات القضاء الشرعي ومجالات القضايا التي ينظرها فبدأت بتعريف القضاء من الناحيتين اللغوية والاصطلاحية، وكذلك استعرضت مشروعية القضاء والأدلة على ذلك من الكتاب والسنة، ومن ثم بينت حكم تولي القضاء، والحكمة من مشروعيته، وبينت أحكام القضاة الوظيفية، وختمت الفصل بالحديث عن معيقات العمل في المحاكم الشرعية. وأما الفصل الثاني فتكلمت عن قوانين الأحوال الشخصية المطبقة في المحاكم الشرعية في فلسطين، فبدأت بالحديث عن القوانين المطبقة في الضفة الغربية وخاصة قانون الأحوال الشخصية الأردني رقم 61 سنة 1976م، ومن ثم استعرضت القوانين المطبقة في قطاع غزة وخاصة قانون حقوق العائلة رقم 303 لسنة 1954م، وختمت الفصل بالحديث عن القوانين المعمول بها في المحاكم الشرعية في فلسطين المحتلة عام 1948م وخاصة قانون حقوق العائلة العثماني لسنة 1917م، وقانون الأحوال الشخصية. واما الفصل الثالث فتكلمت عن التغيرات التي أجريت على قوانين الأحوال الشخصية في المحاكم الشرعية في فلسطين فاستعرضت المواد المضافة والمعدلة في الضفة الغربية، وكذلك المواد المضافة والمعدلة في قطاع غزة، وكذلك المواد المضافة والمعدلة في فلسطين المحتلة عام 1948م، واخيراً تكلمت في نهاية الفصل الثالث عن المواد المقترحة لمشروع قانون الأحوال الشخصية الفلسطيني، فبينت الأسباب الموجبة لوضع المشروع المقترح، والأحكام الموضوعية والإجرائية التي يعالجها المشروع المقترح، ثم ختمت هذه الرسالة بخاتمة تضمنت أهم النتائج والتوصيات، ومن أبرز هذه النتائج أن فقه القضاء هو الذي كان مطبقاً في المحاكم الشرعية في فلسطين إبان فترة حكم الدولة العثمانية، أما بعد صدور التنظيمات لم يبق من صلاحيات للمحاكم الشرعية إلا المسائل المتعلقة بالأحوال الشخصية كالزواج والطلاق والنفقة وغيرها، وأما بقية الاختصاصات من معاملات وجنايات وعقوبات فقد أصبحت من اختصاص المحاكم النظامية، وكذلك من أبرز هذه التوصيات وجوب تطبيق الشريعة الاسلامية في سائر امور المسلمين وأحوالهم، وضرورة توحيد القضاء في فلسطين بأن يصبح قضاءً شرعياً يحكم كل الخلافات، والعمل على توحيد القوانين المطبقة في المحاكم الشرعية في الضفة الغربية وقطاع غزة، ويكون ذلك ضمن مرجعية إسلامية. وكذلك قمت بوضع قائمة لمسارد الرسالة وقائمة للمحتويات وقائمة للمصادر والمراجع.
دراسة عن واقع المحاكم الشرعية وتطور القوانين المعمول بها في فلسطين